Oxford textbook of infectious disease control a geographical analysis from medieval quarantine to global eradication - Cliff, A. D. (Andrew David); Smallman-Raynor, Matthew (Oxford : Oxford University Press, 2013)
This title is a comprehensive analysis of spatial theory and the practical methods used to prevent the geographical spread of communicable diseases in humans. Drawing on current and historical examples spanning seven centuries from across the globe, this indispensable volume demonstrates how to mitigate the public health impact of infections in disease hotspots and prevent the propagation of infection from such hotspots into other geographical locations.
Description based on CIP data; item not viewed.
Keywords: Epidemics -- Prevention; Communicable diseases -- Transmission